2021
DOI: 10.1016/j.proci.2020.06.212
|View full text |Cite
|
Sign up to set email alerts
|

Soot particle size distribution measurements in a turbulent ethylene swirl flame

Abstract: There is a need to better understand particle size distributions (PSDs) from turbulent flames from a theoretical, practical and even regulatory perspective. Experiments were conducted on a sooting turbulent non-premixed swirled ethylene flame with secondary (dilution) air injection to investigate exhaust and in-burner PSDs measured with a Scanning Mobility Particle Sizer (SMPS) and soot volume fractions (fv) using extinction measurements. The focus was to understand the effect of systematically changing the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 29 publications
(63 reference statements)
5
25
0
Order By: Relevance
“…In terms of the total soot number density, N sim s,total , the diluted case shows a decrease of about 60% compared to the undiluted case A, whereas a total SVF leakage, f sim v,total , decrease of about 55% is observed with dilution. Notably, case B shows a total number density of approximately 5.5×10 10 cm −3 and a total SVF of 0.06 ppb, which agree reasonably well with recently obtained experimental measurements at the burner exhaust: N exp s,total = 8.6 × 10 8 ± 1.7 × 10 8 cm −3 , f exp v,total = 0.03 ± 0.01 ppb [28]. Figure 11 shows the comparison between the time-averaged simulated and the measured [28] PSDs obtained at the exhaust.…”
Section: Analysis Of Soot Particle Size Distributionssupporting
confidence: 90%
See 4 more Smart Citations
“…In terms of the total soot number density, N sim s,total , the diluted case shows a decrease of about 60% compared to the undiluted case A, whereas a total SVF leakage, f sim v,total , decrease of about 55% is observed with dilution. Notably, case B shows a total number density of approximately 5.5×10 10 cm −3 and a total SVF of 0.06 ppb, which agree reasonably well with recently obtained experimental measurements at the burner exhaust: N exp s,total = 8.6 × 10 8 ± 1.7 × 10 8 cm −3 , f exp v,total = 0.03 ± 0.01 ppb [28]. Figure 11 shows the comparison between the time-averaged simulated and the measured [28] PSDs obtained at the exhaust.…”
Section: Analysis Of Soot Particle Size Distributionssupporting
confidence: 90%
“…Notably, case B shows a total number density of approximately 5.5×10 10 cm −3 and a total SVF of 0.06 ppb, which agree reasonably well with recently obtained experimental measurements at the burner exhaust: N exp s,total = 8.6 × 10 8 ± 1.7 × 10 8 cm −3 , f exp v,total = 0.03 ± 0.01 ppb [28]. Figure 11 shows the comparison between the time-averaged simulated and the measured [28] PSDs obtained at the exhaust. It is found that in the highdilution case, a fairly good match is obtained with some quantitative differences, also observed from the total soot quantities reported above.…”
Section: Analysis Of Soot Particle Size Distributionssupporting
confidence: 90%
See 3 more Smart Citations